Comprehensive characteristics of pathological subtypes in testicular germ cell tumor: Gene expression, mutation and alternative splicing - Yao, Xiangyang; Zhou, Hui; Duan, Chen; Wu, Xiaoliang; Li, Bo; Liu, Haoran; Zhang, Yangjun (Frontiers in Immunology, 2023)
Background: Testicular germ cell tumor (TGCT) is the most common tumor in young men, but molecular signatures, especially the alternative splicing (AS) between its subtypes have not yet been explored. Methods: To investigate the differences between TGCT subtypes, we comprehensively analyzed the data of gene expression, alternative splicing (AS), and somatic mutation in TGCT patients from the TCGA database. The gene ontology (GO) enrichment analyses were used to explore the function of differentially expressed genes and spliced genes respectively, and Spearman correlation analysis was performed to explore the correlation between differential genes and AS events. In addition, the possible patterns in which AS regulates gene expression were elaborated by the ensemble database transcript atlas. And, we identified important transcription factors that regulate gene expression and AS and functionally validated them in TGCT cell lines. Results: We found significant differences between expression and AS in embryonal carcinoma and seminoma, while mixed cell tumors were in between. GO enrichment analysis revealed that both differentially expressed and spliced genes were enriched in transcriptional regulatory pathways, and obvious correlation between genes and AS events was determined. By analyzing the transcript map and the sites where splicing occurs, we have demonstrated that AS regulates gene expression in a variety of ways. We further identified two pivot transcription-related molecules (SOX2 and HDAC9) involved in AS regulation, which were validated in embryonal carcinoma and seminoma cell lines. Differences in somatic mutations between subtypes are also of concern, with our results suggesting that mutations in some genes (B3GNT8, CAPN7, FAT4, GRK1, TACC2, and TRAM1L1) occur only in embryonal carcinoma, while mutations in KIT, KARS, and NRAS are observed only in seminoma. Conclusions: In conclusion, our analysis revealed the differences in gene expression, AS and somatic mutation among TGCT subtypes, providing a molecular basis for clinical diagnosis and precise therapy of TGCT patients.